Drop-in performance analysis and effect of IHX for an automotive air conditioning system with R1234yf as a replacement of R134a - Direk, Mehmet (Strojniški vestnik, 2017)
This paper presents the experimental comparative performance analysis of an automotive air conditioning (AAC) system using R1234yf and R134a. For this purpose, an AAC experiment setup used for R134a was built to obtain the drop-in performance of a new refrigerant R1234yf. Among the low global warming potential (GWP) refrigerants, R1234yf was particularly chosen due to its similar thermo-physical properties with R134a. However, the system with R1234yf could not perform as efficiently as R134a can. Therefore, an internal heat exchanger (IHX) was employed to enhance the performance of the R1234yf system. After that, the performances of R1234yf and R134a were compared under various compressor speeds and air stream temperatures. The results showed that the cooling capacity and COP of the system with R1234yf were 17.1 % and 12.4 %, respectively, lower compared to the one with R134a. However, when the IHX was introduced into the system with R1234yf, the cooling capacity and COP values were significantly enhanced by 7.9 % and 4.1 %, respectively.
Keywords: avtomobilska hladilna naprava; hladilno število; notranji prenosnik toplote; potencial globalnega segrevanja; R1234yf